Skuteczność i bezpieczeństwo stosowania bevacizumabu w leczeniu wysiękowego zwyrodnienia plamki związanego z wiekiem - Muzyka-Woźniak, Maria; Oficjalska-Młyńczak, Jolanta; Gołębiowska, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To evaluate the efficacy and safety of intravitreal bevacizumab administered on “as required” basis in patients with exudative age-related macular degeneration (AMD). Material and methods: A prospective uncontrolled cohort study of patients with exudative AMD treated with intravitreal bevacizumab administered “as required” based on PRONTO reinjection criteria. Main outcome measures include standardized bestcorrected visual acuity (BCVA) and central macular thickness (CMT) measured with optical coherence tomography (Stratus OCT). Results: 153 eyes of 153 consecutive patients with AMD were treated with intravitreal bevacizumab injection, followed monthly and reinjected “as required”. Mean follow-up time was 14.2 weeks (4-52 weeks). Distance BCVA improved from 0.79 log MAR at baseline to 0.69 at 4 weeks, 0.7 at 8 weeks, 0.64 at 12 weeks, 0.71 at 16 weeks and 0.63 at 20 weeks (p<.05). Near BCVA improved from 0.13 at baseline to 0.22 at 4 and 8 weeks, 0.25 at 12 weeks, 0.22 at 16 weeks and 0.28 at 20 weeks (p<.05). Mean CMT decreased from 395 microm at baseline to 265 at 4 weeks, 260 at 8 weeks, 268 at 12 weeks, 255 at 16 weeks and 257 at 20 weeks (p<.05). Mean time between first and second injection was 91.9 days, and between second and third injection 99.7 days. No adverse events were observed. Conclusions: Short-term results suggest that intravitreal bevaciuzmab administered “as required” is safe and effective in patients with exudative AMD. “As required” schedule may decrease the risk of adverse events and lower the cost of treatment.